Selective flotation separation of chalcopyrite from talc by a novel depressant: N-methylene phosphonic chitosan. (February 2022) - Ye, Wen-Long; Zhang, Xu-Gang; Pan, Cheng-Lin; Hu, Xiu-Qin; Luo, Yong-Chun; Xu, Peng-Fei
Highlights: NMPC can conduct effectively flotation separation of chalcopyrite from talc. NMPC can selectively adsorb on the surface of talc. The flocculation effect of NMPC can accelerate the precipitation of talc. A physisorption process for NMPC– talc interaction is revealed by surface analysis. Abstract: In this work, we investigated the flotation performance and selective adsorption mechanism of a chitosan derivative NMPC (N-methylene phosphonic chitosan) as an novel talc depressant in the flotation separation of chalcopyrite from talc. The single mineral flotation experiments demonstrated that without the talc depressant, both chalcopyrite and talc showed excellent floatability, thus the separation was difficult in the pH range of 3–11. When NMPC was added, the recovery of talc was reduced drastically but the recovery of chalcopyrite decreased slightly in the pH range of 3–9 at a concentration of 10 mg/L in pulp. Artificial mixed mineral flotation experiments also demonstrated that the effective separation of talc and chalcopyrite could be achieved when NMPC was employed as the depressant. The results showed that better grade and recovery were obtained in different proportions of chalcopyrite and talc, which meant the NMPC is better than CMC, Arabic gum in flotation separation of talc and chalcopyrite. Analysis of adsorption tests, FT-IR measurements, and XPS measurements suggested that NMPC was selectively adsorbed on the talc surface by physical adsorption which might result from the hydrogen bonding and hydrophobic interaction between NMPC and talc. Moreover, the sedimentation experiments disclosed that NMPC plays an important role in the flocculation and settling of fine talc.